2014
DOI: 10.1103/physrevlett.113.190404
|View full text |Cite
|
Sign up to set email alerts
|

Self-Guided Quantum Tomography

Abstract: We introduce a self-learning tomographic technique in which the experiment guides itself to an estimate of its own state. Self-guided quantum tomography (SGQT) uses measurements to directly test hypotheses in an iterative algorithm which converges to the true state. We demonstrate through simulation on many qubits that SGQT is a more efficient and robust alternative to the usual paradigm of taking a large amount of informationally complete data and solving the inverse problem of post-processed state estimation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
117
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 15 publications
2
117
0
Order By: Relevance
“…Some approaches seek to avoid unnecessary measurements by assuming that the system is in particular low rank states, such as sparse states [14,15] or low dimensional matrix product states [16]. Alternatively tomography can be 'self-guided', where real-time feedback of measurement results guides the next choice of the measurement basis [17,18], helping to avoid taking measurements that have limited utility for analyzing the state. It has been shown that tomography procedures involving some global quantum measurements have increased error robustness relative to using only local qubit measurements, and thus can be completed in less time [19].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some approaches seek to avoid unnecessary measurements by assuming that the system is in particular low rank states, such as sparse states [14,15] or low dimensional matrix product states [16]. Alternatively tomography can be 'self-guided', where real-time feedback of measurement results guides the next choice of the measurement basis [17,18], helping to avoid taking measurements that have limited utility for analyzing the state. It has been shown that tomography procedures involving some global quantum measurements have increased error robustness relative to using only local qubit measurements, and thus can be completed in less time [19].…”
mentioning
confidence: 99%
“…scales exponentially, and processing of measurement data can be extremely resource demanding. We employ an optimization technique known as the simultaneous perturbation stochastic approximation [31], similar to the algorithm formulated for self-guided quantum state tomography [17]. It minimizes a distance measure between the true state and the algorithm's current guess.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the specific set of rules, also called a policy, according to which the measurement setting s is to be updated, has to be developed separately for each problem at hand. This is true also for the recently developed technique called self-guided quantum tomography (SGQT) [56]. SGQT searches the estimate of a quantum state by making measurements in the directions close to the estimate, approaching it as a power law as a function of adaptive iteration steps.…”
Section: Introductionmentioning
confidence: 99%
“…However, QST is often resource-consuming, involving preparation of a large number of identical unknown states and measurement of a large set of independent observables. For qubit systems, many techniques have been developed to reduce the cost of full state tomography, such as compressed sensing [1][2][3], permutationally invariant tomography [4], self-guided/adaptive tomography [5,6], matrix product states tomography [7]. In contrast, for continuous variable (CV) systems that also play an important role in quantum information, the standard techniques in use today are decades old, namely homodyne measurement [8,9] for optical photons and direct Wigner function measurement [10][11][12] for cavity QED.…”
Section: Introductionmentioning
confidence: 99%